Homeowner Best Management Practices for the Home Lawn - Laurie E. Trenholm (EDIS)
Revised! ENH-979, a 5-page illustrated fact sheet by Laurie E. Trenholm, provides easy-to-follow tips for maintaining a healthy, Florida-Friendly lawn without polluting surface or groundwater resources. Published by the UF Department of Environmental Horticulture, June 2009.